Do not let it derail: the district head's dilemma. Issue 3 (29th June 2021) - Varma, Harikrishnan Ramesh; Kakani, Ram Kumar
Abstract : Theoretical basis: The theoretical concepts and frameworks from the following literature are brought in to discuss the case situation. Freeman's stakeholder framework, Yukl's Influence Tactics, Johnson and Scholes' Power-Interest Matrix Please see: Freeman, R. E. (2010). Strategic Management: A Stakeholder Approach. Pitman Publishing Inc. Yukl, G. (2002). Leadership in Organizations. Prentice-Hall. Johnson, G. and Scholes, K. (1999). Exploring Corporate Strategy: Text and Cases. Prentice-Hall. Research methodology: Information required for the case was primarily collected from Lal Bahadur Shastri National Academy of Administration, Mussorie, India, where the newly recruited civil service officers (probationary trainees) of India are trained. The main protagonist, a senior officer in the Indian Administrative Services was interviewed by one of the authors. Secondary data from contemporary newspaper reports and government orders were also made use of. Case overview/synopsis: Palakkad District Magistrate Gayathri Nair was tasked with acquiring 130 hectares of land for a government-sponsored public-private partnership project to set up a railway coach factory in Palakkad. After taking the landowners into confidence and fast-tracking the administrative process through the line departments, she successfully acquired 93 hectares of land for Phase I of the project. However, the intervention from local politicians and activists halted the next phase. Gayathri was pressured by her bosses to solve the standstill in four weeks. Unable to make the owners realize the benefits of the project, she witnessed a showdown between the agitating masses and the district administration. The entire episode is worsened by the partisan media coverage. The only options open to Gayathri, as the head of the district administration, are either to go ahead with forceful land acquisition and thereby, risk the wrath of the public or abandon the project and bury the months-long back-breaking teamwork. How could Gayathri handle the situation better? What steps could she take at various stages to ensure a balanced outcome for all the stakeholders in the project? Complexity academic level: This case is applicable for the courses/sessions in training programmes for executives, and undergraduate courses related to project management, strategic management, leadership and public policy. It is also useful for courses and training programmes on stakeholder mapping and conflict management.